Psychological distress, depression symptoms and fatigue among Quebec nursing staff during the COVID‐19 pandemic: A cross‐sectional study. Issue 3 (23rd February 2022) - Côté, José; Aita, Marilyn; Chouinard, Maud‐Christine; Houle, Julie; Lavoie‐Tremblay, Mélanie; Lessard, Lily; Rouleau, Geneviève; Gélinas, Céline
Abstract: Aim: To describe the state of health of Quebec nursing staff during the pandemic according to their exposure to COVID‐19, work‐related characteristics and sociodemographic factors (gender, generational age group). State of health was captured essentially by assessing psychological distress, depression symptoms and fatigue. Design and methods: A large‐scale cross‐sectional study was conducted with 1, 708 nurses and licenced practical nurses in Quebec (87% women, mean age of 41 ± 11 years). The survey included several questionnaires and validated health‐related scales (psychological distress, depression symptoms and fatigue). The STROBE guidelines were followed in reporting the study's findings. Results: Results showed that the prevalence of psychological distress and depression symptoms was moderate to severe. Women, generation Xers and Yers, nurses who cared for COVID‐19 patients and those with a colleague who was infected with COVID‐19 at work scored higher for fatigue, psychological distress and depression.